Cycle Related Graphs on Square Difference Labeling - et. al., J. Rashmi Kumar , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, we prove that the graphs cycle with parallel chords, of , Durer-graph, Moser-spindle, Herchel graph are Square difference graph (SDG).